iPhone 4S made simple - Trautschold, Martin; Ritchie, Rene; Mazo, Gary (Apress, 2011)
Congratulations—you've purchased the new iPhone 4S, the coolest smartphone on the market. Now it's time to learn how to take advantage of the new iOS 5 and all its features, apps, and secret techniques available. To accomplish this, look no further than iPhone 4S Made Simple. More than 1,000 screen visuals and clear-cut instructions guide you through both basic and advanced features of the iPhone 4S, from email and calendar tips to navigating the App Store and understanding Bluetooth and Wi-Fi networks. Written by two successful smartphone trainers and authors, this is the go-to guide for the latest and greatest version of the iPhone. This book should also help those who use the popular iPhone 4 or earlier iPhones, that are now running or can run the new iOS 5 operating system as well.